2011
DOI: 10.1038/jhh.2011.27
|View full text |Cite
|
Sign up to set email alerts
|

Limb venous compliance responses to lower body negative pressure in humans with high blood pressure

Abstract: This study tested the hypothesis that limb venous responses to baroreceptor unloading are altered in individuals with high blood pressure (HBP) compared with normotensive (NT) controls. Calf venous compliance was assessed in 20 subjects with prehypertension and stage-1 hypertension (mean arterial pressure, MAP: 104 ± 1 mm Hg) and 13 NT controls (MAP: 86 ± 2 mm Hg) at baseline and during lower body negative pressure (LBNP), using venous occlusion plethysmography. Baroreflex sensitivity (BRS) was measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
7
0
3
Order By: Relevance
“…Present assessments commonly use a mathematically derived quadratic regression equation (QRE) to model the venous pressure-volume curve and the first derivative of this equation to characterize venous compliance. With this approach, venous compliance is bound to become negative at a pressure within or very close to the applied physiological pressure range, precluding a valid interpretation (86)(87)(88)90,92,93). In accordance, we found that 10% of the subjects at 55 mmHg and almost 75% of the subjects at 60 mmHg displayed a negative Ccalf with the QRE.…”
Section: Venous Wall Modelmentioning
confidence: 53%
See 2 more Smart Citations
“…Present assessments commonly use a mathematically derived quadratic regression equation (QRE) to model the venous pressure-volume curve and the first derivative of this equation to characterize venous compliance. With this approach, venous compliance is bound to become negative at a pressure within or very close to the applied physiological pressure range, precluding a valid interpretation (86)(87)(88)90,92,93). In accordance, we found that 10% of the subjects at 55 mmHg and almost 75% of the subjects at 60 mmHg displayed a negative Ccalf with the QRE.…”
Section: Venous Wall Modelmentioning
confidence: 53%
“…The major shortcoming is that the curvilinear pressure-volume relation is fitted to a strict mathematical parabolic function. With this approach, venous compliance is bound to become negative at a pressure within or very close to the applied physiological pressure range, precluding a valid interpretation (86)(87)(88)90,92,93). Due to the form of the venous pressure-volume curve it appears to be of great importance to model the whole curve accurately, especially since gravitational forces could increase venous pressure well above 60 mmHg during prolonged standing.…”
Section: Measurements Of Venous Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…Present assessments commonly use a mathematically derived quadratic regression equation (QRE) to model the venous pressure-volume curve and the first derivative of this equation to characterize venous compliance. With this approach, venous compliance is bound to become negative at a pressure within or very close to the applied physiological pressure range, precluding a valid interpretation (13,17,(32)(33)(34)43).Venous compliance has not been accurately measured in a well-defined VVS population, although lower limb venous pooling may be of pathophysiological importance. The aim of the present study was, therefore, 1) to introduce and validate a new physiologically derived three-parameter venous wall model (VWM) for the characterization of the venous pressure-volume relationship and 2) to accurately study calf venous compliance (C calf ), as well as the calf venous capacitance (V cap ) response (blood pooling), and assess its impact on orthostatic tolerance to lower body negative pressure (LBNP) in women diagnosed with VVS and matched controls.…”
mentioning
confidence: 99%
“…Present assessments commonly use a mathematically derived quadratic regression equation (QRE) to model the venous pressure-volume curve and the first derivative of this equation to characterize venous compliance. With this approach, venous compliance is bound to become negative at a pressure within or very close to the applied physiological pressure range, precluding a valid interpretation (13,17,(32)(33)(34)43).…”
mentioning
confidence: 99%